Design of smart orthosis for rehabilitation of Achilles tendon ruptures - Anderson, Adam (My University, 2025)
Abstract This thesis presents a compact system for measuring forces under the foot, designed for rehabilitation after an Achilles tendon rupture. The aim is that this system could provide patients and care providers with critical data about the recovery process, for a more personalized and effective treatment. The core component of this system is a newly developed flexible insole that senses forces under the foot. The force is measured in three dimensions (i.e., normal and shear forces) using magnetic-based sensors, placed in a grid of 73 nodes. The large area covered by the sensor, and the flexibility, are improvements over previous magnetic-based force measurement systems. The insole and additional support electronics were mounted on a standard ankle orthosis (also known as Walker). In addition, two IMUs were used to estimate the orientation of the insole. Software was also developed to process and visualize the data. The measurements from the insole are sent to a signal processing chain to calculate relevant biomechanics parameters such as the center of pressure and joint torques. The signal processing chain was implemented within ROS2, together with micro-ros for the low-level communication with hardware. ROS2 is also used for visualization purposes. The results are promising, showing that magnetic-based sensors are feasible for measuring 3D forces under the foot. The sensors display a nearly linear response to vertical pressure, although there is considerable hysteresis that introduces errors in the measurements. Future work to improve calibration, verify reliability, and improve ease of use is needed before the system can be used in a clinical setting.
Keywords: Keywords: Plantar pressure, shear force, ROS2, micro-ros, Achilles’ Tendon Rupture, rehabilitation, Hall-effect.